Use of the beta-lactamase inhibitor clavulanic acid in the isolation of auxotrophic mutants of Bacillus licheniformis. - Fields, P I (1984)
The isolation of auxotrophic mutants of Bacillus licheniformis, a microbe containing constitutive beta-lactamase activity, was found to be facilitated by the addition of clavulanic acid and cefotaxime during enrichment.